Observations on the haemopoietic response to critical illness. Issue 10 (October 1990) - Amos, R J; Deane, M; Ferguson, C; Jeffries, G; Hinds, C J; Amess, J A
Abstract : Peripheral blood cytopenias are common in patients receiving intensive care, particularly in those with multiple organ failure. To assess the contribution of bone marrow hypoplasia in such patients 44 bone marrow samples from 24 patients under intensive care were studied by standard morphological techniques and by the granulocyte-macrophage colony forming cell (GM-CFC) assay. Frequently observed morphological abnormalities in the bone marrow included the following: (i) a reduction in overall cellularity in seven patients, with a progressive decrease in most patients studied sequentially; (ii) an increase in the number of actively phagocytic macrophages; and (iii) a disruption of normal bone marrow architecture with the accumulation of intercellular hyaluronic acid glycosaminoglycan. Mean GM-CFC growth was significantly reduced when compared with that in a group of normal controls. In four of five patients studied sequentially GM-CFC growth became subnormal in association with a reduction in bone marrow cellularity. Inhibitory serum factors were not identified. These morphological abnormalities are similar to the changes observed in gelatinous degeneration of the bone marrow. In both situations disruption of the haemopoietic microenvironment, with the accumulation of hyaluronic acid proteoglycan, may be an important factor in the inhibition of haemopoietic progenitor cell growth. The proliferation of macrophages, by the release of a variety of cytokines or reactive oxygen intermediates, may also be implicated in impaired haemopoiesis and the development of disordered erythropoiesis.